2021
DOI: 10.3390/molecules26237398
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Ectodomain G Protein of Respiratory Syncytial Virus and Its Interaction with Heparan Sulfate: Multi-Spectroscopic and In Silico Studies Elucidating Host-Pathogen Interactions

Abstract: The global burden of disease caused by a respiratory syncytial virus (RSV) is becoming more widely recognized in young children and adults. Heparan sulfate helps in attaching the virion through G protein with the host cell membrane. In this study, we examined the structural changes of ectodomain G protein (edG) in a wide pH range. The absorbance results revealed that protein maintains its tertiary structure at physiological and highly acidic and alkaline pH. However, visible aggregation of protein was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 72 publications
(78 reference statements)
2
12
0
Order By: Relevance
“…Therefore, the non-native state of the mutant G protein at pH 2.0 and 3.0 was regarded as an acid-induced molten globule like state. Similar to the mutant protein, the wild-type G protein also formed the molten globule like state at highly acidic pH values in our previous investigation [45]; in both cases, this was attributed to the hydrophobic patches being exposed when the protein was populated at pH 2.0 and 3.0 in the solutions. It was observed that the ANS fluorescence intensity decreased as the pH of the solution moved toward the basic condition (inset of Figure 4).…”
Section: Ans Binding Measurementssupporting
confidence: 61%
See 4 more Smart Citations
“…Therefore, the non-native state of the mutant G protein at pH 2.0 and 3.0 was regarded as an acid-induced molten globule like state. Similar to the mutant protein, the wild-type G protein also formed the molten globule like state at highly acidic pH values in our previous investigation [45]; in both cases, this was attributed to the hydrophobic patches being exposed when the protein was populated at pH 2.0 and 3.0 in the solutions. It was observed that the ANS fluorescence intensity decreased as the pH of the solution moved toward the basic condition (inset of Figure 4).…”
Section: Ans Binding Measurementssupporting
confidence: 61%
“…The thermodynamic stability parameters of mutant G protein are given in Table 1. In our previous investigation, we reported the GdmCl-and urea-induced denaturation of the wild-type G protein [45], in which we found that GdmCl-and urea-induced denaturation followed a two-state transition mechanism. The ∆G D 0 value of the wild-type G protein in the presence of urea was 3.76 ± 0.34 kcal mol −1 ; however, it was found to be 2.87 ± 0.21 kcal mol −1 in the mutant G protein, which indicated that the wild-type G protein was more stable than the mutant G protein in the presence of urea.…”
Section: Gdmcl-and Urea-induced Denaturationmentioning
confidence: 91%
See 3 more Smart Citations